Effect of incubation temperatures on mycelial growth, conidial features and density of Stemphylium botryosum Walr isolates - Subash, S.; Saraswati, N. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The cultural and morphological variability of Stemphylium botryosum Walr was studied with five isolates viz. isolate 1 (Stb-I1), isolate 2 (Stb-I2), isolate 3 (Stb- I3), isolate 4 (Stb-I4) and isolate 5 (Stb-I5) collected from Parsa, Rautahat, Dang, Banke and Chitwan districts of Nepal respectively during 2011-2012 crop season with Completely Randomized Design (CRD) maintaining 3 replications at Plant Pathology Laboratory of Grain Legumes Research Program (GLRP), Rampur, Chitwan. Single spore isolation technique was followed to isolate the pathogen. The pathogen was grow on Potato Dextrose Agar (PDA) and incubated with different temperatures in BOD incubator. The calibrated ocular micrometer was used to measure the length and breadth of the conidia while conidial count with sporulation intensity was attempted with hemocytometer. The mycelium color of the different isolates was varied from white, grey, brown and brownish black in peripheral part while mostly black pigmentation was noticed in lateral part of the culture plate. The shape and texture was regular and velvety for most isolates and in some isolate, roughly irregular shape with cottony texture was found. The higher colony diameter of 7.66 cm and conidial dimension of 29.42×18.12 μm (L/B ratio-1.62) with profuse sporulation intensity (46.67 conidia /0.01 ml) was observed at 25 °C after 15 days of incubation on PDA. However, 2.84 cm diameter, 19.58×9.81 μm (L/B ratio-2.00) with poor conidial density (7.60 conidia /0.01 ml) was noticed at 10 °C. The observation at 10 and 35 °C was at par in case of mycelial growth, conidial features and sporulation intensity. Mostly conidia of all isolates were brown in color at lower incubation temperature but they became dark grey brown at 25 and 30 °C and grey color was noticed when incubated at 35 °C on PDA after 15 days of incubation. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. I, June, 2016, page: 80-89